2016
DOI: 10.1111/1758-2229.12428
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities in Arctic first‐year drift ice during the winter/spring transition

Abstract: Horizontal and vertical variability of first-year drift-ice bacterial communities was investigated along a North-South transect in the Fram Strait during the winter/spring transition. Two different developmental stages were captured along the transect based on the prevailing environmental conditions and the differences in bacterial community composition. The differences in the bacterial communities were likely driven by the changes in sea-ice algal biomass (2.6-5.6 fold differences in chl-a concentrations). Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…In addition, both the bacterial production and abundance correlated with the chl-a concentrations (Spearman's ρ: 0.63, P: 2.291 × 10 − 6 , ρ: 0.83, P: 1.51 × 10 − 11 ), further supporting the coupling between the algal and bacterial communities. The coupling of the sea-ice bacterial community composition and chl-a has been also previously reported in early spring and summer sea ice (Cowie et al, 2014;Eronen-Rasimus et al, 2016). However, a previous mid-winter study showed no correlation between chl-a and bacterial biomass likely because of the low chl-a concentrations in the ice (Stewart and Fritsen, 2004).…”
Section: Resultssupporting
confidence: 68%
“…In addition, both the bacterial production and abundance correlated with the chl-a concentrations (Spearman's ρ: 0.63, P: 2.291 × 10 − 6 , ρ: 0.83, P: 1.51 × 10 − 11 ), further supporting the coupling between the algal and bacterial communities. The coupling of the sea-ice bacterial community composition and chl-a has been also previously reported in early spring and summer sea ice (Cowie et al, 2014;Eronen-Rasimus et al, 2016). However, a previous mid-winter study showed no correlation between chl-a and bacterial biomass likely because of the low chl-a concentrations in the ice (Stewart and Fritsen, 2004).…”
Section: Resultssupporting
confidence: 68%
“…It is a selenoid-shaped photoheterotroph organism, consisting of actinorhodopsin molecules for light energy transduction. After the first isolation, "Candidatus Aquiluna" members were identified in Arctic sea waters, and brackish ice brine [52][53][54][55] and Indian brackish coastal waters [56]. Notably, "Candidatus Aquiluna" was identified as the dominant phylotype in brackish ice brine, which has a lower salinity than immediate sub-ice seawater [55].…”
Section: Taxonomic Profilesmentioning
confidence: 99%
“…For example, the Chukchi Sea is one of the most productive seas on Earth [67]. Some ice-core studies in the Arctic shelf LMEs report dominance of Gammaproteobacteria [68,69], whereas others report dominance of Alphaproteobacteria [53,70] or more or less equal abundances of Gammaproteobacteria, Alphaproteobacteria and Flavobacteriia [64,70]. This variability seems to be independent of the age of the ice (perennial or annual) and more related to the proximity of land, which strongly influences trophic state.…”
Section: Community Structure-bacterial Classesmentioning
confidence: 99%
“…In ice cores from the CAO, Halomonas and Shewanella were extremely rare, with one read each of 12,352 reads [9]. The genus Halomonas consists of salttolerant bacteria [90] and has rarely been reported from the Arctic region [69], whereas more records exist from Antarctica [11,91]. Shewanella has been found in the Arctic region more often, mainly in sediments [92], but also in snow in the CAO [81].…”
Section: Community Structure-dominant Phylotypesmentioning
confidence: 99%
See 1 more Smart Citation